2017
DOI: 10.3928/01913913-20170329-04
|View full text |Cite
|
Sign up to set email alerts
|

Toward Achieving 100% Adherence for Retinopathy of Prematurity Screening Guidelines

Abstract: A computerized system specifically designed with process improvement and error-free delivery of ROP care as a focus can improve adherence to AAP guidelines and achieve superior results. Such a system creates a standardized and measurable safety net for pediatric ophthalmologists, neonatologists, hospitals, and follow-up pediatricians. [J Pediatr Ophthalmol Strabismus. 2017;54(6):356-362.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Additional demographic and medical record data were retrieved from ROP Check software. 11 The Providence NICU utilizes American Academy of Pediatrics (AAP) ROP scheduling guidelines. 12 The smaller and least stable premature infants had additional nursing and respiratory therapy support during exams.…”
Section: Methodsmentioning
confidence: 99%
“…Additional demographic and medical record data were retrieved from ROP Check software. 11 The Providence NICU utilizes American Academy of Pediatrics (AAP) ROP scheduling guidelines. 12 The smaller and least stable premature infants had additional nursing and respiratory therapy support during exams.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies suffer from study [17]. Furthermore, we have previously demonstrated that current AAP screening guidelines performed exceptionally well in providing a safety net for capturing all infants, even those at low risk for severe ROP [15], adding caution to the notion of modifying AAP screening guidelines in a clinical practice setting. Finally, there has been work on a telemedicine approach to addressing ROP workload [10].…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete retinal maturity in an infant otherwise ready for discharge from the NICU places pressures on neonatologists for discharge. Our previous study showed that outpatient ROP care is common in some institutions and that many such infants have advanced ROP and frequently have missed or delayed appointments, making this a high-risk practice for ophthalmologists, neonatologists, NICUs, and primary care pediatricians [15]. Therefore, discharge from NICUs for babies who have not achieved retinal maturity is another potential productive area for quality improvement and collaboration between neonatologists and ophthalmologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One group out of Alaska designed a computerized system specifically designed around ROP with built-in guidelinebased treatment protocols. 6 The benefit of this program was a standardized approach for all stakeholders including the ophthalmologists, neonatologists, hospitals, and general pediatricians.…”
Section: Introductionmentioning
confidence: 99%